KARAKTERISTIK ANATOMI SEL EPIDERMIS DAUN DAN STOMATA TANAMAN KAMBOJA (Plumeria spp.) DI DESA PEMOGAN, KECAMATAN DENPASAR SELATAN, KOTA DENPASAR, BALI: ANATOMICAL CHARACTERISTICS OF LEAF EPIDERMAL CELLS AND STOMATA IN FRANGIPANI PLANTS (Plumeria spp.) IN PEMOGAN VILLAGE, SOUTH DENPASAR DISTRICT, DENPASAR CITY, BALI - Faukha Aisyatur Rahma; Gari, Ni Made; Pharmawati , Made (SIMBIOSIS, 2025)
Frangipani plants (Plumeria spp.) is a member of the Apocynaceae family that can live in various soil conditions. The anatomical structure of frangipani leaves generally consists of epidermis, stomata, trichomes, mesophyll, and vascular bundles. Anatomical characteristics can be used as complementary data in addition to morphological characteristic data in grouping a species. This study aims to determine the anatomical characteristics of leaves from epidermal cells and stomata in seven taxa of frangipani plants located in Pemogan Village, South Denpasar District, Denpasar City, Bali. The study was conducted by observing epidermal cells and stomata in leaf samples taken from the fifth to sixth leaves from the shoot with three leaves each per plant. Observation of epidermal cells and stomata was carried out by the boiling method with 60% nitric acid (HNO3) solution. The results showed that the characteristics of epidermal cells and stomata varied in epidermal cell size, stomata size, and stomatal index. Plumeria spp. has a polygonal epidermis (quadrilateral - octagonal) with irregular edges. The stomata are of the parasitic type, characterized by two neighboring cells located parallel to the guard cells, and are found in abundance on the adaxial and abaxial parts of the leaves in the six cultivars observed, except in P. obtusa L Singapore, where stomata were only found on the abaxial part of the leaves. Key word: Frangipani, anatomy, epidermal cells, stomata